From burnout to involvement of medical staff. Strategies for successful creation of an effective organizational culture in a medical institution (practical cases of the Mayo Clinic) - Naumenko Галина (Psychosomatic Medicine and General Practice, 2020)
The health care system is changing rapidly in an effort to provide quality care, improve public health, and optimize spending on patients with chronic diseases and the elderly. Changes affecting clinical practice include new approaches to payment and supply of medicines, electronic medical records, patient portals and public reports on quality indicators. Leaders of the transformation are health professionals, whose daily work is crucial for the success and improvement of the Health Care system. It should be borne in mind that the consequence of systemic medical changes and the resulting additional pressure may be professional burnout of health workers. To prevent burnout, it is necessary to develop the involvement of staff, which should not be only the personal responsibility of the health worker, but form a comprehensive approach to the interaction of the organization and employees. That is why the mistake of many medical institutions is to start with narrowed decisions for the formation of staff involvement. For example, through trainings, seminars on stress management, etc. Healthcare professionals perceive these actions as insincere intentions of the medical institution in solving problems. The organization must demonstrate by its actions and example the concern for the well-being of its employees (creation of recreation areas, transparent system of rewards and feedback, optimization / automation of processes to simplify work, etc.). Using the experience of the Mayo Clinic*, this article will discuss 9 effective strategies to achieve this goal. * The Mayo Clinic is a non-profit organization (an organization that does not have the main purpose of its activities to make a profit and does not distribute the profits among the participants), one of the largest private medical and research centers in the world, founded in 1889. As of 2012, the Mayo Clinic is an exemplary medical center, employing 50.9 thousand people, including 3,800 doctors and scientists. The clinic’s revenue in 2012 exceeded 8.8 billion; about 500 million is allocated for research. Medical facilities under the auspices of the Mayo Clinic operate in 70 cities in the United States, the largest units - in Phoenix and Jacksonville.